The impact on judicial independence in Mexico after the 2024 constitutional reform: a legal-constitutional reflection - Martín Guardado, Sergio (2025)
The constitutional reform of the Judiciary in Mexico, enacted in 2024, represents an unprecedented structural change that seriously affects the principle of judicial independence, a cornerstone of the rule of law and constitutional democracy. This reform introduces the popular election of judges, magistrates, and Supreme Court justices; eliminates the Federal Judiciary Council; restructures the Supreme Court; and alters the rules of access, tenure, and judicial discipline itself. Under the guise of enhancing the democratic legitimacy of justice, the reform weakens the principles of impartiality, professionalism, and separation of powers, placing the judge within a logic of political representation that is foreign to the nature of the judicial function.This article analyzes the effects of this institutional transformation from a dogmatic legal perspective, arguing that the new model breaks with the counter-majoritarian logic that must prevail within the judiciary by seeking to align and subordinate it to political cycles and electoral contingencies.